Assessment of the glenohumeral joint's active and passive axial rotational range. - Humphries,A; Cirovic,S; Bull,AM; Hearnden,A; Shaheen,AF (Journal of Shoulder and Elbow Surgery, 2015)
BACKGROUND: Assessment of the range of axial rotation of the glenohumeral joint will improve understanding of shoulder function, with applications in shoulder rehabilitation and sports medicine. However, there is currently no complete description of motion of the joint. The study aimed to develop a reliable protocol to quantify the internal and external axial rotations of the glenohumeral joint during active and passive motion at multiple humeral positions. METHODS: Optical motion tracking was used to collect kinematic data from 20 healthy subjects. The humerus was positioned at 60°, 90°, and 120° of humerothoracic elevation in the coronal, scapular, and sagittal planes. Internal and external rotations were measured at each position for active and passive motion, where intrasubject standard deviations were used to assess variations in internal-external rotations. RESULTS: The protocol showed intrasubject variability in the axial rotational range of <5° for active and passive rotations at all humeral positions. Maximum internal rotation was shown to be dependent on humeral position, where a reduced range was measured in the sagittal plane (P < .001) and at 120° elevations (P < .001). Conversely, maximum external rotations were not affected by humeral position. CONCLUSION: The results describe normal ranges of internal-external rotation of the glenohumeral joint at multiple humeral positions. The protocol's low variability means that it could be used to test whether shoulder pathologic conditions lead to changes in axial rotational range at specific humeral positions.